Health Outcomes of Infants in a PMTCT Program in Kinshasa. (September 2015) - Ditekemena, John; Matendo, Richard; Colebunders, Robert; Koole, Olivier; Bielen, Gabrielle; Nkuna, Michel; Engmann, Cyril; Tshefu, Antoinette; Ryder, Robert; ,
Effective follow-up of mother–infant pairs is critical for ensuring the success of preventing mother-to-child transmission (PMTCT) programs. The objective of this study was to identify factors associated with health outcomes of exposed infants in a PMTCT program in the Democratic Republic of Congo (DRC). Data were collected from January 2005 through December 2008 in 2 maternities in Kinshasa, DRC. The exposed infant's health status was used as outcome. Multiple logistic regressions were used to identify the determinants of infant outcomes. A total of 309 mother–infant pairs were included in this study. Younger maternal age, breast-feeding but weaning before the age of 6 months, and HIV testing of the child and a mother who is not sick were associated with better infant health outcome. The follow-up of mother–infant pairs in PMTCT programs remains critical and challenging. There is a need for innovative and efficient strategies to improve retention of mother–infant pairs in PMTCT programs.